Injury-Related Consequences of Alcohol Misuse among Injured Patients who Received Screening and Brief Intervention for Alcohol: A Latent Class Analysis. Issue 2 (April 2014) - Cochran, Gerald; Field, Craig; Caetano, Raul
Background: Screening and brief alcohol intervention has demonstrated efficacy in improving drinking and other risk behaviors for some patient populations. However, it is not clear that brief interventions are helpful to all injured patients who drink at risk levels. This paper identifies latent classes of intervention recipients based on injury-related consequences and risks of alcohol misuse and then determines which profiles experienced the greatest improvements in drinking. Methods: A secondary analysis was conducted using data from injured patients ( N = 737) who reported heavy drinking and received a brief alcohol intervention in a Level I trauma center. Latent class analysis was used to determine patient profiles, and 7 indicators commonly associated with alcohol-related injury from the Short Inventory of Problems+6 were used to determine the latent class measurement model. Covariates were regressed onto the model to assess factors related to class membership, and drinking outcomes were analyzed to examine improvements in drinking. Results: Five classes emerged from the data. The classes that reported the greatest improvements in drinking following discharge were those characterized by multiple alcohol-related risks and those characterized by a history of alcohol-related accidents and injuries. Attributing the current injury to drinking was a significant predictor of class membership among those classes that reported higher levels of improvement. Conclusions: This study provides tentative evidence that subclasses exist among heavy drinking injured patients who received a brief intervention in a Level I trauma center, and some subclasses experience greater drinking improvements than others. Further research is required to substantiate the findings of this secondary analysis.